Analisis Faktor yang Mempengaruhi Indeks Pembangunan Manusia (IPM) Jawa Timur 2021 Menggunakan Metode Regresi Logistik Ordinal - Muhammad Firza Ibnu Hartono; Laelatul Khikmah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In order to improve the welfare and prosperity of the population, local governments make efforts known as regional development. One of the tools used to measure this progress is the human development index. The purpose of this study is to determine the human development index in each district or city in East Java in 2021. Some variables that are thought to affect the human development index include the open unemployment rate, labor force participation rate, poverty rate, life expectancy, average years of schooling and expected years of schooling.